2021
DOI: 10.3390/agronomy11061234
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Environmental Factors for the Development of Water Erosion of Soil in Agricultural Land: The Southern Part of Hronská Pahorkatina Hill Land, Slovakia

Abstract: The water erosion research was carried out in the lowland type of hilly landscape. The aim was to monitor and evaluate the importance of environmental factors (steepness of slope, relief shapes, aspect, slope length, combination slope length (L) and slope (S)—LS factor, types of land use changes) for the development of water erosion. We focused on the identification of areas threatened by erosion by interpreting aerial photographs from several time periods. This was followed by verification of erosion using so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 59 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…We found that almost all soils on slopes with a slope less than 3 • were accumulated and eroded on slopes with a slope greater than 3 • . Similar research results, in which there were significant manifestations of erosion in moderately rugged upland parts, were documented by [10]. To identify dominant factors, respectively, under the conditions of erosion activity the average depths of humus horizons of individual soil types were determined as follows:…”
Section: Field Soil Researchmentioning
confidence: 70%
See 1 more Smart Citation
“…We found that almost all soils on slopes with a slope less than 3 • were accumulated and eroded on slopes with a slope greater than 3 • . Similar research results, in which there were significant manifestations of erosion in moderately rugged upland parts, were documented by [10]. To identify dominant factors, respectively, under the conditions of erosion activity the average depths of humus horizons of individual soil types were determined as follows:…”
Section: Field Soil Researchmentioning
confidence: 70%
“…Great emphasis on preventing the effects of water erosion activity by modeling soil erosion (which makes it possible to anticipate erosion and prevent soil erosion) was presented by the Slovak authors [7,8]. Foreign authors dealt with this issue, especially [9,10]. Landscape modeling as well as regional development issues are discussed in [11][12][13][14] and others.…”
Section: Introductionmentioning
confidence: 99%
“…More erosion monitoring is essential to inform long-term soil conservation in this region [3]; however, obtaining the raw field data of soil erosion in the region remains challenging. Many types of monitoring methods are available, such as erosion pins [4,5], runoff plots [6,7], 3D laser scanners [8,9], real-time kinematic (RTK)-GPS [10,11], aerial photos or remote sensing [12,13], and tracers [14,15]. Equations for predicting soil erosion have also been developed, such as the universal soil loss equation or revisions thereof [16][17][18].…”
Section: Introductionmentioning
confidence: 99%